Method for determining impurity content in zirconium oxide
By combining zirconium and hafnium as matrix by DC glow discharge mass spectrometry, the problem of determining impurity elements in high-purity zirconia is solved, and a fast, reliable and accurate measurement is achieved, meeting the needs of high-purity material analysis.
Patent Information
- Application Number
- CN202411788616.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to quickly, reliably and accurately determine impurity elements in high purity zirconia, especially when the impurity concentration is low and the matrix element concentration is high.
By using DC glow discharge mass spectrometry, the content of the element to be measured is calculated by pretreating and presputting high-purity zirconium oxide, selecting zirconium and hafnium as matrix, setting the isotope and resolution of the element to be measured, and the DC glow discharge mass spectrometry analysis and testing is performed, and the ratio coefficient factor k is calculated to calculate the element to be measured.
It realizes rapid, reliable and accurate measurement of impurity elements in high-purity zirconia. The lower limit of measurement can reach ppb level, and the analysis cycle is significantly shortened, meeting the requirements of modern high-purity material analysis tests for reliability, accuracy and rapid multi-element analysis.
Smart Images

Figure BDA0005176036640000021 
Figure BDA0005176036640000031 
Figure BDA0005176036640000061
Abstract
Description
Technical Field
[0001] The invention relates to a method for determining impurity elements in zirconium oxide, in particular to a method for determining impurity elements in high-purity zirconium oxide by direct current glow discharge mass spectrometry. Background Art
[0002] Zirconia has the characteristics of high melting point, wear resistance, corrosion resistance, etc. It is an excellent functional and structural material, widely used in technical fields such as aviation, atomic energy and optical fiber communication. The performance and application of zirconium oxide are closely related to its impurity content, and the chemical composition of zirconium oxide directly affects its performance. At present, the main goal of the development of my country's zirconium industry is to take into account the needs of civil zirconium and high-purity zirconium, and establish a detection, evaluation and quality assurance system for high-purity zirconium materials.
[0003] At present, the methods for analyzing the chemical composition of zirconium oxide are mainly gravimetric method, photometric method, atomic absorption spectrometry, inductively coupled plasma emission spectrometry, and inductively coupled plasma mass spectrometry. These methods have a long analysis period, cumbersome analysis steps, and involve many chemical reagents. In the current analysis method, the determination of the main element content of zirconium and zirconium alloys adopts the mandelic acid gravimetric method, and the determination range is 75%-99%. This method cannot meet the purity requirements. Analysis of high-purity zirconium oxide above 99.99%, and the analysis cycle is long; for other impurity elements, photometric method, atomic absorption spectrometry, and inductively coupled plasma emission spectrometry have low determination efficiency and high determination lower limit, which cannot meet the needs of high-purity material testing and analysis. Inductively coupled plasma mass spectrometry uses microwave digestion to dissolve samples, which can meet the needs of high-purity material testing and analysis, but the digestion requirements are high, and it takes about three days to complete the entire analysis.
[0004] There are two main challenges in impurity analysis of high-purity materials: first, the impurity concentration is low, which requires the instrument to have high detection capability, background control and interference elimination capabilities; second, the concentration of matrix elements is high, which easily interferes with the measured elements. Glow discharge mass spectrometry (GDMS) detection equipment, such as the GDMS double-focusing high-resolution mass spectrometer, has the characteristics of low detection limit, wide linear range and simultaneous determination of multiple elements, and is suitable for constant, trace, trace and ultra-trace analysis. At present, there is mature experience in using glow discharge mass spectrometry to analyze trace impurities in samples, and analysis standards for materials such as high-purity copper, high-purity titanium, and high-purity aluminum have been formed.
[0005] Mo Shumin et al. established a GDMS analytical method for determining 36 trace impurity elements such as Na, Al, Si, P, Ti, V, Cr, and Fe in high-purity zirconium in "Determination of 36 trace impurity elements in high-purity zirconium by glow discharge mass spectrometry" (Metallurgical Analysis. 2019, 39(5): 13-18), and used this method to determine the trace impurity elements in high-purity zirconium samples. Summary of the invention
[0006] The object of the present invention is to provide a method for rapidly, reliably and accurately determining impurity elements in high-purity zirconium oxide.
[0007] The object is achieved by a method for determining impurity elements in high-purity zirconium oxide using direct current glow discharge mass spectrometry, the method comprising:
[0008] 1) Pre-treating high-purity zirconium oxide to obtain a sample to be tested;
[0009] 2) Pre-sputtering the sample to be tested;
[0010] 3) Select zirconium and hafnium as the matrix and set the isotope and resolution of the element to be measured;
[0011] 4) performing a DC glow discharge mass spectrometry test; and
[0012] 5) The sum of the signals generated by zirconium and hafnium is defined as 100%, and the content of the element to be measured is calculated according to the ratio k of the signal intensity of the element to be measured and the sum of the signal intensities obtained by zirconium and hafnium. The ratio coefficient factor k is calculated according to formula ①:
[0013]
[0014] Among them, M (Zr+Hf) is the sum of the relative molecular masses of zirconium and hafnium;
[0015] It is the sum of the relative molecular masses of zirconium dioxide and hafnium dioxide. DETAILED DESCRIPTION
[0016] Before describing several exemplary embodiments of the invention, it is to be understood that the invention is not limited to the details of construction or process steps described in the following description. The invention is capable of other embodiments and of being practiced or carried out in various ways.
[0017] For terms used in this specification, the following definitions are provided.
[0018] Throughout the specification including the claims, the term "comprising a" or "including an" should be understood to be synonymous with the term "comprising at least one", unless otherwise specified, and "between" or "to" should be understood to include the limit values.
[0019] The terms "a," "an," and "the" are used to refer to one or more than one (ie, to at least one) of the grammatical object of the clause.
[0020] The term "and / or" includes the meanings "and", "or" and also all other possible combinations of the elements related to this term.
[0021] All percentages and ratios are stated by weight unless otherwise indicated.
[0022] The term "mixture" or "composition" as used herein refers to but is not limited to any combination in any physical or chemical form, such as blends, solutions, suspensions, alloys, composites, and the like.
[0023] In a first aspect of the present invention, the present invention relates to a method for determining impurity elements in high-purity zirconium oxide using direct current glow discharge mass spectrometry, the method comprising:
[0024] 1) Pre-treating high-purity zirconium oxide to obtain a sample to be tested;
[0025] 2) Pre-sputtering the sample to be tested;
[0026] 3) Select zirconium and hafnium as the matrix and set the isotope and resolution of the element to be measured;
[0027] 4) performing a DC glow discharge mass spectrometry test; and
[0028] 5) The sum of the signals generated by zirconium and hafnium is defined as 100%, and the content of the element to be measured is calculated according to the ratio k of the signal intensity of the element to be measured and the sum of the signal intensities obtained by zirconium and hafnium. The ratio coefficient factor k is calculated according to formula ①:
[0029]
[0030] Among them, M (Zr+Hf) is the sum of the relative molecular masses of zirconium and hafnium;
[0031] It is the sum of the relative molecular masses of zirconium dioxide and hafnium dioxide.
[0032] The term "high purity zirconia" is used to refer to high purity zirconium dioxide (ZrO2) materials, which are usually used in high-end applications such as electronics, optics, ceramics, catalysts and biomedicine. The purity of high purity zirconia is generally 99.99% or higher, which means that its impurity content is extremely low, which can ensure its performance and stability in specific applications.
[0033] In one embodiment of the present invention, the pre-treatment includes tableting the high-purity zirconium oxide powder using a tableting mold.
[0034] In one embodiment of the present invention, the tablet pressing mold comprises: an upper mold, a cathode block and a lower mold.
[0035] In a specific embodiment of the present invention, the tablet pressing mold structure is as described in Utility Model Patent Application No. 202421204431.5. The tablet pressing mold is suitable for glow discharge mass spectrometry detection of conductive powder samples and non-conductive powder samples, and can be easily demoulded and recovered powder samples.
[0036] Utility model patent application No. 202421204431.5 provides a tablet pressing mold, including:
[0037] An upper die, comprising a pressing head and a pressing head rod arranged above the pressing head;
[0038] A cathode block, made of a conductive material, comprising a pressing plate hole passing through the cathode block, wherein the cross-sectional dimension of the pressing plate hole corresponds to the cross-sectional dimension of the pressing head;
[0039] A lower mold, comprising a tableting position and a demolding position, wherein the tableting position comprises at least one tableting plane for tableting, and the demolding position comprises a demolding groove for receiving a sample, wherein the cross-sectional dimension of the demolding groove is smaller than the cross-sectional dimension of the cathode block;
[0040] Wherein, when the tablet pressing mold is in the tablet pressing configuration, the cathode block is arranged at the tablet pressing position of the lower mold, and the pressing head can pass through the tablet pressing hole of the cathode block and rest on the tablet pressing plane; when the tablet pressing mold is in the demolding configuration, the cathode block is arranged at the demolding position of the lower mold, and the pressing head can pass through the tablet pressing hole of the cathode block and extend into the demolding groove.
[0041] In a preferred embodiment of the present invention, each component of the tablet pressing mold is made of niobium metal or tantalum metal, wherein the purity of the niobium metal or tantalum metal used to make the cathode block is above 99.999%. However, it is understood that they can be made of other materials as long as they are suitable for detection needs.
[0042] In a specific embodiment of the present invention, the cathode block is made of niobium metal with a purity of more than 99.999%, and the content of a single impurity element (such as lithium, boron, sodium, magnesium, aluminum, silicon, calcium, titanium, vanadium, chlorine, manganese, iron, nickel, copper, zinc, etc.) is not more than 0.05ppm.
[0043] In a specific embodiment of the present invention, the metal selected as the cathode block is tantalum with a purity of more than 99.999%, and the content of individual impurity elements (such as lithium, boron, sodium, magnesium, aluminum, silicon, calcium, titanium, vanadium, chlorine, manganese, iron, nickel, copper, zinc, etc.) other than niobium is not more than 0.05ppm.
[0044] In a specific embodiment of the present invention, in order to avoid the introduction of contamination, the tableting mold is placed in an inorganic strong acid solution to clean and remove surface contaminants before tableting, then rinsed with deionized water, cleaned with an organic reagent, blown dry with nitrogen, and set aside.
[0045] The inorganic strong acid is selected from one or more combinations of hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid and chloric acid.
[0046] In a more preferred embodiment of the present invention, the inorganic strong acid is electronically pure (MOC) hydrofluoric acid. In another more preferred embodiment of the present invention, the inorganic strong acid is a mixed acid of hydrofluoric acid and nitric acid, wherein the volume ratio of hydrofluoric acid to nitric acid is 1:1 to 3:1, including 5:4, 3:2 and 2:1.
[0047] The organic reagent is selected from one or more combinations of acetone, isopropanol, methanol, ethanol, dichloromethane, carbon tetrachloride, n-hexane, cyclohexane and chloroform.
[0048] In a preferred embodiment of the present invention, the pressure applied to the high-purity zirconium oxide for tableting is 0.1-0.9 tons, including 0.2, 0.3, 0.4, 0.5, 0.6 and 0.8 tons. The number of tableting is 2-8 times, including 3, 4, 5, 6 and 7 times, and the high-purity zirconium oxide to be tested is pressed into a flat sheet-shaped high-purity zirconium oxide sample to be tested.
[0049] In one embodiment of the present invention, the pre-sputtering discharge current is 25-50 mA, including 30, 35, 40 and 45 mA, preferably 35-45 mA, and more preferably 40 mA.
[0050] In one embodiment of the present invention, the pre-sputtering discharge gas flow rate is from 400-550 mL / min, including 420, 440, 460, 480, 500 and 520 mL / min, preferably 450-500 mL / min, more preferably 480 mL / min.
[0051] In one embodiment of the present invention, the pre-sputtering time is greater than or equal to 3 minutes, preferably greater than or equal to 5 minutes.
[0052] In one embodiment of the present invention, the analytical test includes selecting a resolution mode according to interference conditions of the elements to be measured in the glow discharge mass spectrum.
[0053] In a specific embodiment of the present invention, when collecting the elements to be tested, the resolution MR>4000 and HR>10000 are required. For the elements with mass spectrum interference: K, Ti, As, Se, Nb, Ir, Pt, Au, Pd, Cd, Ag, among which K, Ti, As, Se, Nb, Ir, Pt, Au are tested at high resolution, and for Pd with 94 Zr 16 O, 92 Zr 16 O, 90 Zr 16 O interferes, so the present invention selects isotope 105 Pd is tested; for Cd 94 Zr 16 Oh, 92 Zr 16 Oh, 94 Zr 16 Oh, 94 Zr 17 Oh, 96 Zr 17 Oh, 96 Zr 18 Oh, 90 Zr 16 O, so the present invention selects 116 Cd is tested; for Ag 90 Zr 17 Oh, 92 Zr 17 Oh, 91 Zr 18 Oh, 94 Zr 16 O interference; both isotopes are interfered by oxides, and the interference cannot be removed by selecting isotopes. Therefore, the present invention selects 109 Ag, and introduce the interference equation for offline processing correction: 109 Ag= 109 [I] -10.1321× 113 [I]+0.4552× 115 [I], where 109 [I] is the mass spectrum signal value measured at mass number 109, in cps (counts per second); 113 [I] is the mass spectrum signal value measured at mass number 113, in cps; 115 [I] is the mass spectrum signal value measured at mass number 115, in cps.
[0054] In one embodiment of the present invention, the method further comprises calculating the purity of high-purity zirconium oxide by the following formula ②:
[0055]
[0056] in, The purity of high-purity zirconium oxide is the sum of the content of ZrO2+HfO2.
[0057] C x is the test content of element x in ppm,
[0058] C (x,Ta) is the content of element x in high purity niobium or high purity tantalum, in ppm
[0059] ∑ Element It is the sum of the contents of all elements to be measured, in ppm, minus the contents of the corresponding elements in high purity niobium or high purity tantalum, in ppm.
[0060] The present invention provides a method for rapidly determining impurity elements in non-conductive high-purity zirconium oxide and determining purity by using direct current glow discharge mass spectrometry. The use of high-purity metals for sample preparation simplifies the cumbersome sample pre-treatment steps, avoids the introduction of contamination, and the lower limit of determination can reach the ppb level. At the same time, the present invention sets appropriate parameters and optimizes the method for interfering elements in mass spectrometry analysis, calculates the oxide ratio factor of zirconium-hafnium binary oxide in a bundling manner, and establishes a purity calculation formula. The method meets the requirements of modern high-purity material analysis and testing for reliability, accuracy, and rapid analysis of multiple elements.
[0061] Specifically, the present invention relates to the following embodiments:
[0062] 1. A method for determining impurity elements in high-purity zirconium oxide using direct current glow discharge mass spectrometry, the method comprising:
[0063] 1) Pre-treating high-purity zirconium oxide to obtain a sample to be tested;
[0064] 2) Pre-sputtering the sample to be tested;
[0065] 3) Select zirconium and hafnium as the matrix and set the isotope and resolution of the element to be measured;
[0066] 4) performing a DC glow discharge mass spectrometry test; and
[0067] 5) The sum of the signals generated by zirconium and hafnium is defined as 100%, and the content of the element to be measured is calculated according to the ratio k of the signal intensity of the element to be measured and the sum of the signal intensities obtained by zirconium and hafnium. The ratio coefficient factor k is calculated according to formula ①:
[0068]
[0069] Among them, M (Zr+Hf)is the sum of the relative molecular masses of zirconium and hafnium;
[0070] It is the sum of the relative molecular masses of zirconium dioxide and hafnium dioxide.
[0071] 2. A method as described in Embodiment 1, wherein the pretreatment includes pressing high-purity zirconium oxide using a tableting mold.
[0072] 3. A method as described in Embodiment 2, wherein the tablet pressing mold comprises: an upper mold, a cathode block and a lower mold.
[0073] 4. A method as described in Embodiment 3, wherein the various components of the tablet pressing mold are made of niobium metal or tantalum metal, wherein the purity of the niobium metal or tantalum metal used to make the cathode block is above 99.999%.
[0074] 5. A method as described in embodiments 2-4, wherein the pressure applied to the high-purity zirconium oxide for tabletting is 0.1 to 0.9 tons.
[0075] 6. A method as described in embodiments 1-5, wherein the pre-sputtering discharge current is 25-50 mA.
[0076] 7. A method as described in embodiments 1-6, wherein the pre-sputtering discharge gas flow rate is from 400-550 mL / min.
[0077] 8. A method as described in embodiments 1-7, wherein the pre-sputtering time is greater than or equal to 3 minutes, preferably greater than or equal to 5 minutes.
[0078] 9. As described in embodiments 1-8, the analytical test includes selecting a resolution mode according to the interference of the element to be measured in the glow discharge mass spectrometer.
[0079] 10. The method according to embodiments 4-9 further comprises calculating the purity of high-purity zirconium oxide by the following formula ②:
[0080]
[0081] in, The purity of high-purity zirconium oxide is the sum of the content of ZrO2+HfO2.
[0082] C x is the test content of element x in ppm,
[0083] C (x,Ta) is the content of element x in high purity niobium or high purity tantalum, in ppm
[0084] ∑ ElementIt is the sum of the contents of all elements to be measured, in ppm, minus the contents of the corresponding elements in high purity niobium or high purity tantalum, in ppm.
[0085] Example
[0086] The present invention is illustrated using the following examples, which, however, are not to be construed as limiting the scope of the invention.
[0087] Place the high-purity tantalum plate in a mixed acid (HNO3:HF=1:1), clean it with a reaction to remove surface pollutants, take it out and rinse it with deionized water, then clean it with acetone, blow it dry with nitrogen, and set it aside. Place high-purity zirconium oxide powder with a purity of 99.99% into the tablet hole of a tablet mold made of high-purity tantalum, put it into a press, and press it with a pressure of 0.5 tons for 3 times to make a flat sheet sample to be tested. Prepare six tablet samples in parallel. Blow away the floating and sinking on the surface of the tablet sample with nitrogen, and put it into the sample pool. Use an Element GD Plus glow discharge mass spectrometer for testing, and measure it according to the parameters in Table 1 to collect the signals of the elements to be tested and the matrix elements Zr and Hf.
[0088] Table 1 Instrument operating parameters
[0089]
[0090] Input the ratio coefficient factor of the element to the oxide calculated in formula ①, and the instrument automatically determines the content of the element to be measured, and deducts the content of the corresponding impurity element in high-purity tantalum on this basis to obtain the actual content of the impurity element in high-purity zirconium oxide. To ensure the reliability of the results, this experiment was measured six times and the precision was statistically calculated. In addition, tantalum blocks were used as blank samples for the determination of the detection limit. The specific results are shown in Table 2.
[0091] The verification experiment was carried out using an inductively coupled plasma mass spectrometer, and the experimental method was carried out in accordance with the standard YS / T568.12-2022. The parameters are also shown in Table 1. Some elements were verified, and the results are also listed in Table 2.
[0092] In addition, the comparative experiment uses the same sample preparation and detection process as in the embodiment, except that hafnium is not selected as the matrix in the comparative experiment, and the measurement is performed according to the parameters in Table 1 to collect the signals of the element to be measured and the matrix element Zr. The measurement results are also shown in Table 2.
[0093] Table 2 Comparison of test results
[0094]
[0095]
[0096] The experimental results show that when hafnium is not selected as the matrix, most of the measurement results are too high, and the measurement results of some impurity elements to be measured deviate greatly from the results of inductively coupled plasma mass spectrometry, failing to accurately reflect the true value. In contrast, the method of the present invention uses zirconium and hafnium as matrix internal standards, and the measured results are within the range of 0.001 to 0.1ppm, with a precision within 150%, while the precision of other orders of magnitude does not exceed 80%. Compared with the results of inductively coupled plasma mass spectrometry, the two methods have a high consistency in the measurement results of the same order of magnitude, and the measurement results of some elements are very close.
[0097] Finally, the purity of zirconium oxide was calculated to be 99.992% by formula ②, which is consistent with the expected value of the sample. The overall analysis time of this experiment only takes one day. Compared with wet analysis and inductively coupled plasma mass spectrometry, the present invention significantly shortens the analysis cycle and improves efficiency.
Claims
1. A method for determining impurity elements in high-purity zirconium oxide using direct current glow discharge mass spectrometry, the method comprising: 1) Pre-treating high-purity zirconium oxide to obtain a sample to be tested; 2) Pre-sputtering the sample to be tested; 3) Select zirconium and hafnium as the matrix and set the isotope and resolution of the element to be measured; 4) performing a DC glow discharge mass spectrometry test; and 5) The sum of the signals generated by zirconium and hafnium is defined as 100%, and the content of the element to be measured is calculated according to the ratio k of the signal intensity of the element to be measured and the sum of the signal intensities obtained by zirconium and hafnium. The ratio coefficient factor k is calculated according to formula ①: Among them, M (Zr+Hf) is the sum of the relative molecular masses of zirconium and hafnium; It is the sum of the relative molecular masses of zirconium dioxide and hafnium dioxide.
2. The method according to claim 1, wherein the pretreatment comprises pressing the high-purity zirconium oxide into tablets using a tabletting mold.
3. The method of claim 2, wherein the tabletting mold comprises: Upper die, cathode block and lower die.
4. The method according to claim 3, wherein each component of the tablet pressing mold is made of niobium metal or tantalum metal, and the purity of the niobium metal or tantalum metal used to make the cathode block is above 99.999%.
5. The method according to claims 2-4, wherein the pressure applied to the tableting of the high-purity zirconium oxide is 0.1 to 0.9 tons.
6. The method according to claims 1-5, wherein the pre-sputtering discharge current is 25-50 mA.
7. The method of claims 1-6, wherein the pre-sputtering discharge gas flow rate is from 400-550 mL / min.
8. The method according to claims 1-7, wherein the pre-sputtering time is greater than or equal to 3 minutes, preferably greater than or equal to 5 minutes.
9. The method according to claims 1 to 8, wherein the analytical test comprises selecting a resolution mode according to interference conditions of the element to be measured in the glow discharge mass spectrometer.
10. The method according to claims 4-9, further comprising calculating the purity of high-purity zirconium oxide by the following formula ②: in, The purity of high-purity zirconium oxide is the sum of the content of ZrO2+HfO2. C x is the test content of element x in ppm, C (x,Ta) is the content of element x in high purity niobium or high purity tantalum, in ppm ∑ Element It is the sum of the contents of all elements to be measured, in ppm, minus the contents of the corresponding elements in high purity niobium or high purity tantalum, in ppm.
Citation Information
Cited By
Method for determining impurity content in zirconia
WO2026119029A1